2015
DOI: 10.1177/1745691614556679
|View full text |Cite
|
Sign up to set email alerts
|

A Person-Centered Approach to Moral Judgment

Abstract: Both normative theories of ethics in philosophy and contemporary models of moral judgment in psychology have focused almost exclusively on the permissibility of acts, in particular whether acts should be judged on the basis of their material outcomes (consequentialist ethics) or on the basis of rules, duties, and obligations (deontological ethics). However, a longstanding third perspective on morality, virtue ethics, may offer a richer descriptive account of a wide range of lay moral judgments. Building on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
304
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(355 citation statements)
references
References 85 publications
28
304
2
1
Order By: Relevance
“…The motivation of moral judgment is ultimately about judging others' moral character -one should avoid interacting with a person who is perceived to be immoral. The bad luck the first manager experienced may be informative about character: being reckless or imprudent, for example, means the manager deserves to be blamed (Uhlmann et al, 2015). This is also consistent with the research on the belief in lucklucky or unlucky outcomes are associated with perceived personal characteristics (Day & Maltby, 2003;Maltby et al, 2008).…”
Section: Luck As Undeservedsupporting
confidence: 74%
See 2 more Smart Citations
“…The motivation of moral judgment is ultimately about judging others' moral character -one should avoid interacting with a person who is perceived to be immoral. The bad luck the first manager experienced may be informative about character: being reckless or imprudent, for example, means the manager deserves to be blamed (Uhlmann et al, 2015). This is also consistent with the research on the belief in lucklucky or unlucky outcomes are associated with perceived personal characteristics (Day & Maltby, 2003;Maltby et al, 2008).…”
Section: Luck As Undeservedsupporting
confidence: 74%
“…Each perspective is closely tied to a particular literature that entails as yet unsolved puzzles that suggest promising directions for future research. For example, while prior studies in psychology uniformly suggest that people tend to mistake luck for skill when evaluating performance differences (Baron & Hershey, 1988;Kahneman, Slovic, & Tversky, 1982;Langer, 1975;Nisbett & Ross, 1980;Rosenzweig, 2007;Ross & Nisbett, 1991), recent studies point at an asymmetry in the evaluations between successes and failures (Denrell & Liu, 2012;Pizarro, Uhlmann, & Salovey, 2003;Uhlmann, Pizarro, & Diermeier, 2015). While people appreciate the role of (bad) luck in failures, they do not necessarily do the same when it comes to explaining success.…”
Section: About Herementioning
confidence: 99%
See 1 more Smart Citation
“…This practice is supported by data demonstrating a relationship between conviction rates and whether a jury learned of a defendant's previous crimes (Eisenberg & Hans, 2009) and by studies showing that conviction rates are greater when the previous crimes are related to the present one (Wissler & Saks, 1985). More directly, experimental evidence suggests that blame and perceived causation are increased by general information about the defendant's bad moral character and that these relationships are mediated by emotional reactions to the character information (Nadler, 2012;Uhlmann, Pizarro, & Diermeier, 2015). Finally, studies have shown that blame and causal judgments are influenced by global dispositional information (such as likableness) in addition to dispositional information that is related to a specific offense (e.g., an aggressive personality matched to an aggressive crime; Alicke & Yurak, 1995;Alicke & Zell, 2009).…”
Section: Type Of Offense and Scope Of Evidencesupporting
confidence: 56%
“…Social observers are highly motivated to obtain information about the moral qualities of others (Uhlmann, Pizarro, & Diermeier, 2015). Affective states and displays provide social information of moral relevance that the observer can utilise to make inferences about the moral character of the target, and their propensity to undertake relevant behaviours that signal character (Szczurek, Monin, & Gross, 2012;Uhlmann et al, 2015;Watson-Jones & Legare, 2016).…”
Section: Attracting Moral Judgments From Observersmentioning
confidence: 99%